Leveraging cultural heritage to develop the integration of GLAM in Indonesian universities - Dinastiti Kusuma Budi; Fajrina Nur Aulia; Khairani Amalia; Kurniasih Yuni Pratiwi (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction: This research aims to develop an understanding of GLAM integration in university environments in Indonesia by highlighting how the utilization of cultural heritage can serve as a foundation for building an integrated GLAM ecosystem. Research Methods: A systematic literature review approach was used, collecting data through the Google Scholar and Researchgate search engines using keywords related to GLAM, cultural heritage, universities, and integration. A total of seven articles from international and national journals, research reports, and other publications were analyzed in this study. Data Analysis: The data were qualitatively analyzed through a comprehensive literature review. Sources were identified and synthesized to understand GLAM’s role in promoting and preserving cultural heritage. Results: GLAM integration in universities can foster cultural understanding and appreciation among students. Challenges include limited awareness, funding, infrastructure, and supportive policies. Successful implementation in European universities shows improved access and engagement with cultural heritage.Conclusions: GLAM contributes significantly to cultural heritage preservation in universities. However, Indonesian institutions face challenges such as lack of awareness, funding, and infrastructure. Recommended strategies include enhancing collaboration, developing digital collections, and initiating cultural programs. The establishment of a GLAM Center, educational initiatives, local community involvement, and active promotion are expected to strengthen heritage preservation and foster multicultural awareness in Indonesian society.